Influence of high magnetic field on access to stationary H-modes and pedestal characteristics in Alcator C-Mod. (7th February 2018) - Tolman, E.A.; Hughes, J.W.; Wolfe, S.M.; Wukitch, S.J.; LaBombard, B.; Hubbard, A.E.; Marmar, E.S.; Snyder, P.B.; Schmidtmayr, M.
Abstract: Recent Alcator C-Mod experiments have explored access to and characteristics of H-modes at magnetic fields approaching 8 T, the highest field achieved to date in a diverted tokamak. The H-modes originated from L-mode densities ranging from 1.1 × 10 20   m − 3 to 2.8 × 10 20   m − 3, allowing insight into the density dependence of the H-mode power threshold at high magnetic field. This dependence is compared to predictions from the ITPA scaling law ([001 ]), finding that the law is approximately accurate at 7.8 T. However, the law underpredicted the high density H-mode threshold at lower magnetic field in previous C-Mod experiments ([002 ]), suggesting that the overall dependence of the threshold on magnetic field is weaker than predicted by the scaling law. The threshold data at 7.8 T also indicates that the onset of a low density branch at this magnetic field on C-Mod occurs below 1.4 × 10 20   m − 3, which is lower than predicted by an existing model for low density branch onset. The H-modes achieved steady-state densities ranging from 2.3 × 10 20   m − 3 to 4.4 × 10 20   m − 3, and higher transient densities, and had values of q 95 from 3.3 to 6.0. This parameter range allowed the achievement of all three types of H-mode routinely observed at lower magnetic field on C-Mod: the stationary, ELM-suppressed Enhanced D α (EDA) regime, seen at high densities and high values of q 95 ; the nonstationary ELM-free regime, seen at lower densities and values of q 95 ; and the ELMy regime, seen at low density, moderate q 95, and specialized plasma shape. The parameter space in which these regimes occur at 7.8 T is consistent with lower magnetic field experience. Pressure pedestal height at 7.8 T is compared to EPED [003, 004 ] predictions, and a scaling law for EDA density pedestal height developed between 4.5 T and 6.0 T is updated to include fields from 2.7 T to 7.8 T. Overall, this analysis increases confidence in the use of low magnetic field experience to predict some elements of high magnetic field tokamak behavior.